2020
DOI: 10.1080/21655979.2020.1768694
|View full text |Cite
|
Sign up to set email alerts
|

From stale bread and brewers spent grain to a new food source using edible filamentous fungi

Abstract: By-products from the food sector with a high load of organic matter present both a waste-handling problem related to expenses and to the environment, yet also an opportunity. This study aims to increase the value of stale bread and brewers spent grain (BSG) by re-introducing these residues to the food production chain by converting them to new protein-enriched products using the edible filamentous fungi Neurospora intermedia and Rhizopusoryzae . After 6 days of sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 84 publications
5
50
0
Order By: Relevance
“…This is in line with research that has reported the smell of products made of edible filamentous fungi, such as N. intermedia, to be generally pleasant [51]. The fungi burger patties that are cultivated on bread residuals predominately smell of mushrooms but also have a nutty and fruity smell [34], which seems to be perceived as pleasant by many participants.…”
Section: Perceptions On the Fungi Burger Pattysupporting
confidence: 86%
See 2 more Smart Citations
“…This is in line with research that has reported the smell of products made of edible filamentous fungi, such as N. intermedia, to be generally pleasant [51]. The fungi burger patties that are cultivated on bread residuals predominately smell of mushrooms but also have a nutty and fruity smell [34], which seems to be perceived as pleasant by many participants.…”
Section: Perceptions On the Fungi Burger Pattysupporting
confidence: 86%
“…Preliminary laboratory research using bread residues resulted in a fungi burger patty, which has promising qualities for human consumption in terms of its texture and nutritive quality [34]. In fact, the protein content of bread can be more than doubled after fermentation for five days using the edible filamentous N. intermedia [34]. As earlier mentioned, the production of meat-based food requires large amounts of resources.…”
Section: Fungi Cultivation On Bread Residualsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing population on Earth results in protein depletion regarding food and feed sources. Protein-rich biomass, which can be obtained from, e.g., edible yeast, bacteria, and filamentous fungi, represents a potential alternative protein source for feed and food applications [16,17]. In the previous studies, it has been stated that N. intermedia, a GRAS (generally regarded as safe) microorganism, can be used for the production of nutritious food products from stale bread and brewers spent grains [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Protein-rich biomass, which can be obtained from, e.g., edible yeast, bacteria, and filamentous fungi, represents a potential alternative protein source for feed and food applications [16,17]. In the previous studies, it has been stated that N. intermedia, a GRAS (generally regarded as safe) microorganism, can be used for the production of nutritious food products from stale bread and brewers spent grains [17,18]. The product made in the form of a burger has led to general acceptance during sensorial analysis in terms of taste and structure but also regarding waste valorization perspectives [17,18].…”
Section: Introductionmentioning
confidence: 99%